2022
DOI: 10.1080/07853890.2022.2118368
|View full text |Cite
|
Sign up to set email alerts
|

Association between dyslipidaemia and the risk of hyperuricaemia: a six-year longitudinal cohort study of elderly individuals in China

Abstract: Background Despite abundant evidence linking dyslipidaemia to an increased risk of hyperuricaemia, the exact association between each component of dyslipidaemia and hyperuricaemia remains controversial. Thus, the objective of this research was to examine the correlation between dyslipidaemia and its components, as well as hyperuricaemia in Chinese people over the age of 60. Methods In this study, 4018 participants over 60 years without hyperuricaemia were investigated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Elevated TG levels may result in an increase in free fatty acids and a faster breakdown of adenosine triphosphate, both of which lead to an increase in uric acid 40 . Xu et al found that high TG and low HDL-C were significantly and independently associated with the risk of HUA in a 6-year prospective study of Chinese older adults over 60 years old, and that there was a nonlinear increasing trend among TG, HDL-C, and SUA 41 . Hou et al found that the risk of HUA in patients with high TG was 2.353 times that in patients with normal TG.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated TG levels may result in an increase in free fatty acids and a faster breakdown of adenosine triphosphate, both of which lead to an increase in uric acid 40 . Xu et al found that high TG and low HDL-C were significantly and independently associated with the risk of HUA in a 6-year prospective study of Chinese older adults over 60 years old, and that there was a nonlinear increasing trend among TG, HDL-C, and SUA 41 . Hou et al found that the risk of HUA in patients with high TG was 2.353 times that in patients with normal TG.…”
Section: Discussionmentioning
confidence: 99%
“…Serum uric acid has been reported to be elevated in patients with hypertension, diabetes, and dyslipidemia, and hyperuricemia is an independent predictor for various cardiovascular diseases. 5,50,51 The multiple logistic regression analysis with adjustment for blood pressure, total cholesterol, triglycerides, and glucose showed that serum uric acid levels were associated with TAA and TAD risks. The uratelowering drug allopurinol prevented TAAD development in the widely used BAPN-induced and Ang II-induced mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated TG levels may result in an increase in free fatty acids and a faster breakdown of adenosine triphosphate, both of which lead to an increase in uric acid 40 . Xu et al found that high TG and low HDL-C were signi cantly and independently associated with the risk of HUA in a 6-year prospective study of Chinese older adults over 60 years old, and that there was a nonlinear increasing trend among TG, HDL-C, and SUA 41 . Hou et al found that the risk of HUA in patients with high TG was 2.353 times that in patients with normal TG.…”
Section: Discussionmentioning
confidence: 99%